2010
DOI: 10.1128/aac.01554-09
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Amphotericin B and Echinocandins as Monotherapy or Sequential or Concomitant Therapy in Murine Disseminated and Pulmonary Aspergillus fumigatus Infections

Abstract: Monotherapy and combination therapy were compared using optimal doses of liposomal amphotericin B, micafungin, or caspofungin in Aspergillus fumigatus pulmonary and disseminated infections. Mice were challenged intravenously (2.8 ؋ 10 4 to 5.7 ؋ 10 4 conidia) or intranasally (5.8 ؋ 10 7 conidia) with A. fumigatus. Drugs (5, 10, or 15 mg/kg of body weight) were given for 3 or 6 days as single, concomitant, or sequential therapy (i.e., days 1 to 3 and then days 4 to 6). Mice were monitored for survival, and tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 61 publications
(68 reference statements)
4
18
1
Order By: Relevance
“…These results are similar to the present results, as the maximum effect (100% survival) was reached at a dose of 4 or 16 mg/kg for all isolates. Our observations are also in keeping with previously published experimental studies of aspergillosis (18,19,(36)(37)(38)(39)(40). Leenders et al reported that in a pulmonary aspergillosis infection in rats, L-AmB monotherapy at 5 and 10 mg/kg was effective in preventing dissemination from the lungs to the kidneys, liver, and spleen (36).…”
Section: Discussionsupporting
confidence: 82%
“…These results are similar to the present results, as the maximum effect (100% survival) was reached at a dose of 4 or 16 mg/kg for all isolates. Our observations are also in keeping with previously published experimental studies of aspergillosis (18,19,(36)(37)(38)(39)(40). Leenders et al reported that in a pulmonary aspergillosis infection in rats, L-AmB monotherapy at 5 and 10 mg/kg was effective in preventing dissemination from the lungs to the kidneys, liver, and spleen (36).…”
Section: Discussionsupporting
confidence: 82%
“…Several animal studies demonstrated the benefit of using a dual combination of LAmB and echinocandins or LAmB and Def over monotherapy in treating IPA (9,17,24) or mucormycosis (8,10,22), while others showed an indifferent effect (23). We show in this study that triple combination therapy consistently enhanced survival and reduced the tissue fungal burden of mice infected with mucormycosis compared to placebo, monotherapy, or dual drug therapy.…”
mentioning
confidence: 52%
“…13 Although intracerebral or intravenous infections are not assumed to play an important natural route for the acquisition of invasive aspergillosis, such infections are frequently used to test the efficiency of antifungal drugs and to study the dissemination and disease progression in brain and kidneys. [5][6][7]14 The ability to detect luminescence from all deep tissues including liver and kidneys is an essential prerequisite for a potential use of luminescence based systems for monitoring drug efficiency from in vivo conditions. Our previous studies using an intranasal infection model revealed a localization of fungi that was mainly restricted to the lung and, in some cases, the nasal sinus.…”
Section: Discussionmentioning
confidence: 99%